Balance Report and Solvency Ratio Analysis of PT. Ekadharma International Tbk. Period 2018-2020 - Rahmadini, Nurhaliza (Indonesian Operations Research Association (IORA), 2021)
PT. Ekadharma International Tbk. is a company that expands its business into the adhesive tape industry in meeting the needs of the Indonesian market. The development of this company must also be balanced with its financial stability. The source of information used to measure the company's financial condition is financial statements. The benchmark used in this research is vertical analysis and solvency ratio analysis which shows the company's ability to pay its obligations when the company is liquidated. The types of ratios used are Debt to Asset Ratio and Debt to Equity Ratio. Vertical analysis shows that the total assets of PT. Ekadharma International Tbk. always increase from year to year. While the results of the calculation of the solvency ratio show that the percentage is in a relatively small number, namely 10%-20% and always decreases every year. By presenting data that has been processed and interpreted, this balance sheet report can provide good insight for the company, employees, and shareholders in making economic decisions for the company.